Investigating the Link between Economic Complexity Index and Monetary Policy Lending Rates in Selected Sub-Saharan African Countries - Ralarala, O.; Ncanywa, T. (Journal of Reviews on Global Economics, 2019)
This article investigates if there is a link between economic complexity index and monetary policy lending rates in selected Sub-Saharan African countries. Economic complexity index (ECI) as a measure of productive capabilities and a mix of sophisticated products that countries export, has been found to influence some economic indicators such as economic growth and inequality. Little attention has been paid to ECI’s link to lending rates in monetary policy bank lending rate transmission mechanism. In this paper, the ECI-lending rate nexus has been investigated using a panel autoregressive distribution lag methodology. Results indicated a long-run significant relationship with the Kao and Johansen combined cointegration. It was further illustrated in the long-un that ECI estimates have a negative and significant impact on monetary policy lending rates. The series could correct to equilibrium at a significant rate of 25%. These results provided new insights needed for appropriate development economic policy to reduce monetary policy lending rates.